2012
DOI: 10.3389/fmicb.2012.00046
|View full text |Cite
|
Sign up to set email alerts
|

Infection Strategies of Bacterial and Viral Pathogens through Pathogen–Human Protein–Protein Interactions

Abstract: Since ancient times, even in today’s modern world, infectious diseases cause lots of people to die. Infectious organisms, pathogens, cause diseases by physical interactions with human proteins. A thorough analysis of these interspecies interactions is required to provide insights about infection strategies of pathogens. Here we analyzed the most comprehensive available pathogen–human protein interaction data including 23,435 interactions, targeting 5,210 human proteins. The data were obtained from the newly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 47 publications
4
71
0
Order By: Relevance
“…In this scenario, bacteria may have adapted to attack proteins involved in specific pathways, most importantly in immunity and defence mechanisms34. However, whether protein–protein interactions with the host are correlated to pathogen fitness during infection is currently unknown.…”
mentioning
confidence: 99%
“…In this scenario, bacteria may have adapted to attack proteins involved in specific pathways, most importantly in immunity and defence mechanisms34. However, whether protein–protein interactions with the host are correlated to pathogen fitness during infection is currently unknown.…”
mentioning
confidence: 99%
“…For example, the Y2H methodology is biased for certain types of interactions in a non-native environment [34], binding events may or may not be biologically relevant, and statistical testing is hampered by small effect sizes and small statistical power. Conversely, this and previous studies have shown that multiple pathogens tend to target the same host proteins, biological processes, and pathways [2, 9, 10, 18]. Hence, one could potentially use common pathogenic mechanisms to more robustly characterize bacterial proteins and their host targets.…”
Section: Resultsmentioning
confidence: 88%
“…For instance, although human host interactors of viruses and bacteria range across all biological functions, common or pathogen specific themes can be observed within pathogenic groups by meta-analysis of HP-PPI studies. First, viral proteins and to a lesser extent secreted bacterial effector proteins [30], are both more likely to interact with host hub proteins (highly connected proteins in the host network) [16,17,21] and bottleneck proteins (central proteins to many signaling pathways) [10,31,67] for an increased efficiency in altering host cellular processes. Secondly, by performing gene ontology enrichment analysis on the host targets, viral pathogens seems to unavoidably disturb cellular processes as they rely on the transcriptional machinery, whereas bacteria tend to mesh with the immune response to prevent their clearance [10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some bacterial pathogens such as certain Shigella dysenteriae or Escherichia Coli strains express Shiga toxins generally during their lytic cycle [8] or release these toxins through Outer Membrane Vesicles during their growth phase [9], leading to the inhibition of protein synthesis or activation of the apoptotic pathways of their host cells. As the number of bacterial host-pathogen interaction studies increases, they demonstrate that while bacteria generally do not rely on host cell machinery for the purpose of replication as directly as viruses do, they do seem to disrupt the immune response [10] and interact preferentially with the hosts’ cytoskeleton as a mean of motility, invasion of the host tissues [11] and escape of phagocytic cells [12]. For instance, Mycobacterium tuberculosis (Mtb), an intracellular parasite, is known to modulate the host’s immune response and prevent its bacterial clearance by suppression of autophagy.…”
Section: Introduction To Host-pathogen Protein-protein Interactionsmentioning
confidence: 99%